State Responsibility for the Citizens in Indoensia’s Covid-19 Pandemic - Rachmat Dwi Putranto; Gunawan Nachrawi; Marjan Miharja; Mayang Maharani Yahya Bayan; Jean Magtel Pah (Budapest International Research and Critics University, 2021)
This Covid-19 pandemic has elevated Indonesia to emergency status, prompting the government to implement an emergency PPKM policy, as detailed in Minister of Home Affairs Instruction 15 of 2021 on the enactment of restrictions on community activities in the Java and Bali provinces. However, the strategy does not imply that the government is abdicating its duty for all facets of citizens' life. This legal research examines the laws and regulations governing the treatment of the Covid-19 epidemic in Indonesia using the conceptual approach and the statute approach. This legal research draws on secondary primary law sources, including statutes and regulations pertaining to the legal topics covered, as well as legal publications such as textbooks, legal dictionaries, legal journals, and other legal literature.